Comparison of conservative against surgical treatment of anterior–superior iliac spine avulsion fractures in children and adolescents - Kautzner, Jakub (Springer Berlin Heidelberg, 2014)
PURPOSE: Avulsion fracture of the anterior–superior iliac spine is an uncommon injury. It is mostly seen in adolescent sprinters, distance runners and soccer players. Most cases are unilateral. We present a cohort of patients and the strategy for their treatment. METHODS: During the period 2005–2012, we treated 23 (19 male, four female) patients with an average age of 15.1 years (4–17). Ten patients with minimally displaced fractures were treated conservatively, and 13 patients with greater fragment dislocation were treated surgically. All patients underwent the standardised rehabilitation protocol. We evaluated range of motion (ROM), X-ray six weeks and one year postoperatively, length of bed rest, return to activity and complication rates (infection, heterotopic ossification). RESULTS: All patients returned to sports at the preinjury level. Surgically treated patients showed faster recovery and better compliance with rehabilitation protocols. The time interval for X-ray union was comparable between groups, as was full recovery. There was no deep infection; however, there were five minor heterotopic ossifications, none of which required further treatment. CONCLUSION: We emphasise that the indication for surgical treatment is mainly determined by the grade of fragment displacement and the patient’s sporting activity. Although long-term results were comparable between treatment methods, surgery carries the risk of higher complication rates and the need for osteosynthetic material extraction.